Uogólniona miara odległości GDM a współczynnik korelacji liniowej Pearsona i cosinus kąta między wektorami - Walesiak, Marek (The generalised distance measure GDM and Pearson correlation coefficient and the cosine of the angle between vectors, 2005)
The paper gives based on relation between squared Euclidean distance and Pearson correlation coefficient (the cosine of the angle between vectors), similar proposals for Generalised Distance Measure GDM.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 18-26